Laser 2. Uses in Ophthalmology - Muhammad, Shad (Journal of Postgraduate Medical Institute, 2011)
Ophthalmologists have been in the forefront for developing medical applications for new laser technology since the construction of the first laser in 1960. Photocoagulation was the earliest therapeutic laser procedure and it remains the one most widely employed. there are a number of ocular applications, primarily in the retina but also in the anterior segment and the details of most of these clinical therapeutics will be discussed in this paper.